Digital Labor-Market Intermediation and Job Expectations: Evidence from a Field Experiment - Ana C. Dammert; Jose C. Galdo; Virgilio Galdo (Institute for the Study of Labor (IZA), 2013)
Subjective expectations are fundamental for understanding individual behavior. Yet, little is known about how individuals use new information to formulate and update their subjective expectations. In this study, we exploit data from a multi-treatment field experiment to investigate how job-market information sent to jobseekers via short text messages (SMS) influence subjective job gain expectations in Peru. Results show that jobseekers who received digital intermediation based on a large information set increased their before-after job gain expectations relative to the control group. Independently of the information channel, no significant effects were found when labor-market intermediation is based on a restricted (short) set of information.
Keywords: I3; J2; 330; subjective expectations; labor-market intermediation; ICT; field experiments; Peru